Tester och Utvärdering av BactiQuant - För analys av bakteriehalter i vattenströmmar hos Göteborg Energi - Bengtsson Braun, Amanda (My University, 2023)
Sävenäsverket is one of all Göteborg Energi's facilities around the city. Electricity and heat are produced here with the help of a bio boiler. To make use of the energy contained in the flue gases, these are condensed, and the condensate is further purified. The purification process takes place in several stages with help of different filters and membranes. In recent years, Göteborg Energi has had problems with high levels of bacteria in the flue gas condensate. The bacteria form biofilms, clog parts of the process and destroy filters and membranes. By improving their ability to monitor the bacteria levels, Göteborg Energi would be able to implement faster actions against the bacteria growth. To make this possible, a bacteria sampling instrument has been rented from the company BactiQuant. This instrument has been tested and compared against other analytical methods for bacterial sampling. Partly by sending samples to an external laboratory and partly by growing bacteria on agar plates. Samples have been taken at several test points in the water treatment. It has been investigated whether it is possible to compare BQW with cfu/ml, how different operating conditions affect bacteria levels, if the instrument provides financial benefits and how the working hours look relative to these. At many test points, no result has been obtained by the BactiQuant instrument. Because of this, it has also been studied if there is anything that can interfere with the analysis. Since analysis values have not been given in all places, it is difficult to draw a conclusion about how good the instrument really is for Göteborg Energi. It would provide flexibility, better control of bacterial levels and environmental benefits. However, it is not possible to say how relevant the results really are without further studies.
Keywords: BactiQuant; teria analysis; flue gas condensate; BQW